2014
DOI: 10.7314/apjcp.2014.15.17.7055
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Apoptotic Effects of Extracts of Artemisia ciniformis Krasch. & Popov ex Poljakov on K562 and HL-60 Cell Lines

Abstract: Asian Pac J Cancer Prev, 15 (17), [7055][7056][7057][7058][7059] IntroductionIncrease in prevalence of cancer cases has been associated with the expansion of industrial, chemical and radioactive pollutants, also the gap between human being and nature (Colditz and Wei, 2012; Fasinu and Orisakwe, 2013). Despite the progress in the field of medicinal chemistry and development in the synthesis of several new therapeutic compounds, the role of plants and phytochemicals can not be ignored in pharmaceutical science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Transgenic plants were analyzed to consider their taxadiene production. Results demonstrate the possibility of genetic engineering of the taxane biosynthetic pathway in Artemisia annua L. for the production of taxadiene (42, 43). …”
Section: Resultsmentioning
confidence: 84%
“…Transgenic plants were analyzed to consider their taxadiene production. Results demonstrate the possibility of genetic engineering of the taxane biosynthetic pathway in Artemisia annua L. for the production of taxadiene (42, 43). …”
Section: Resultsmentioning
confidence: 84%
“…MCF-7 cells were cultured in 25 t-flask and were maintained in Dulbecco's modified Eagle's medium supplemented with 100 IU/ mL penicillin, 100 μg/mL streptomycin, 10% fetal bovine serum at 37°°C with 5% CO 2 , 95% air and complete humidity [28].…”
Section: Mtt-assay Proceduresmentioning
confidence: 99%
“…Also, pretreatment with sesamol enhances the irradiation efficacy in HeLa cells (11). Artemisia species are popular and traditional herbal medicines for the treatment of a variety of diseases and there have been a number of studies on their biological activities (12). Recent studies have shown the anticancer effect of some species of Artemisia, such as A. ciniformis (12) and A. absinthium (13).…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia species are popular and traditional herbal medicines for the treatment of a variety of diseases and there have been a number of studies on their biological activities (12). Recent studies have shown the anticancer effect of some species of Artemisia, such as A. ciniformis (12) and A. absinthium (13). Another study has reported the cytotoxic effect of A. indica in four cancer cell lines, namely A-549, Caco-2, THP-1, and HEP-2 (14).…”
Section: Introductionmentioning
confidence: 99%